Analysis of Inundation area as an Impact of Sea Level Rise in Kota Pariaman District, West Sumatera Province - Putri, Elsa Eka; Galib, Musrifin; Mubarak, Mubarak (Journal of Coastal and Ocean Sciences, 2021)
This research has conducted on February 2021 in Kota Pariaman District, Sumatera Barat Province. The intention of this research was to found out the sea level rise rate based on tidal data analysis from 2001-2020 and to predict the inundation area in the 20th, 50th, and 80th to go. The method of this research was a descriptive survey by using remote sensing as the additional equipment to demonstrate the outcome. The acquisition needs are primary (land use and tidal data) and secondary (slope, elevation, land use, and tidal data) data. Those parameters were processed and analyzed to describe the area of inundation by displaying a map of Kota Pariaman. Kota Pariaman territorial water has 0,44 of Formzhal number which means the waters area is classified to mixed semidiurnal tides with the sea level rise value reach out to 2,006 cm/year. Then, the number used to predict the height of sea-level rise in 20th, 50th, and 80th to go, for each is 0,471 m; 1,073 m; and 1,675m. Furthermore, the sea level rise height was analyzed to get the inundation area in 20th, 50th, and 80th to go, turns out the flooded area for each year respectively to 14,56 ha; 23,61 ha, and 38,16 ha.